Critical current density of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 superconductor irradiated with neutron in in-core facilities: rotary rack and dry tube at PUSPATI TRIGA Research Reactor - Mujaini M.; Ilhamsyah A.B.P.; Muhammad-Najib K.; Hamid N.A.; Awang R.; Idris F.M.; Bayar A.M.J.; Hamzah N.S.; Abd-Shukor R. (Springer Science and Business Media Deutschland GmbH, 2024)
The effects of neutron irradiation in dry tube (DT) and rotary rack (RR) facilities at PUSPATI TRIGA Reactor on the superconducting properties of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 (Bi-2223) are reported. The samples were prepared via the co-precipitation method and exposed to neutron irradiation in both facilities for 0.25h to 5h with neutron flux 6.90 1012 and 2.75 1012 n cm?2s?1, respectively. The structure, microstructure, radionuclide, electrical resistance, and AC susceptibility were determined. Energy-dispersive X-ray analysis revealed the presence of Zn and Po due to the neutron activation. Gamma spectroscopy analysis showed that neutron irradiation produced 85Sr radionuclide. The electrical resistance showed onset temperature, Tc-onset of 118K and transport critical current density, Jc-t of 2.14 A cm?2 at 50K for the non-irradiated sample. AC susceptibility showed that the transition temperature, Tc?? was around 106 to 109K and 105 to 109K for samples irradiated in DT and RR facilities, respectively. The lower peak temperature, TpL of the imaginary part of the susceptibility, ?? varied from 88 to 97K. Sample irradiated for 4h with neutron fluence of 3.96 1016 n cm?2 in RR facility showed the highest Jc-t (15.88 A cm?2 at 50K). Samples irradiated in RR showed higher Jc-t compared with samples irradiated in DT facility. Neutron irradiation suppressed the transition temperature and Bi-2223 phase, but improved Jc-t by more than six times in DT and seven times in RR facility. The optimal neutron fluence for neutron irradiation in Bi-2223 was between 2.48 1016 and 3.96 1016 n cm?2. 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.